RIPK1 in necroptosis and recent progress in related pharmaceutics - Yao, Kunhou; Shi, Zhihao; Zhao, Fengya; Tan, Cong; Zhang, Yixin; Fan, Hao; Wang, Yingzhe; Li, Xingwang; Kong, Jun; Wang, Qun; Li, Dingxi (Frontiers in Immunology, 2025)
Necroptosis is a programmed form of cell death. Receptor-interacting serine/threonine protein kinase l (RIPK1) is a crucial protein kinase that regulates the necroptosis pathway. Increased expression of death receptor family ligands such as tumor necrosis factor (TNF) increases the susceptibility of cells to apoptosis and necroptosis. RIPK1, RIPK3, and mixed-lineage kinase-like domain (MLKL) proteins mediate necrosis. RIPK1-mediated necroptosis further promotes cell death and inflammation in the pathogenesis of liver injury, skin diseases, and neurodegenerative diseases. The N-terminal kinase domain of RIPK1 is significant in the induction of cell death and can be used as a vital drug target for inhibitors. In this paper, we outline the pathways of necroptosis and the role RIPK1 plays in them and suggest that targeting RIPK1 in therapy may help to inhibit multiple cell death pathways.